(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Plants are crucial in human health and welfare especially in the developing African countries. Medicinal and cultural importance of Spondias mombin and Rauvolfia vomitoria were investigated in this study. A pre-tested questionnaire was used to extract information from Ninety nine (99) purposively selected informants in six communities. Resulting data was analyzed using simple frequency, utilization tables, charts and Pearson correlation analysis on SPSS package. Results showed that 93.9% and 97.0% of the respondents have lived in the area for more than five years and are familiar with the study plants respectively. Ethno-medicinal citations revealed stomach disorder (11) and Malaria (9) as the main uses of S. mombin while Malaria (18) and Hemorrhoid (10) are the main ailments managed with R. vomitoria. Non-medicinal uses include; live fences, shade for artisans, edible fruits, carving farm implements handles, local building construction and dye production. There is a significant positive correlation (0.637) in the utilization awareness of S. mombin and R. vomitoria. The plants are perceived to be scarce in the wild while roots were mostly used for local medicine. The two plant species have potentials for development of affordable drugs to stem prevalent malaria infections. Domestication, sustainable harvesting and further research into conservation of the plant species are recommended.